The discovery and characterization of AeHGO in the branching route from shikonin biosynthesis to shikonofuran in Arnebia euchroma - Wang, Ruishan; Liu, Changzheng; Lyu, Chaogeng; Sun, Jiahui; Kang, Chuanzhi; Ma, Ying; Wan, Xiufu; Guo, Juan; Shi, Linyuan; Wang, Jinye; Huang, Luqi; Wang, Sheng; et al. (Frontiers in Plant Science, 2023)
Shikonin derivatives are natural naphthoquinone compounds and the main bioactive components produced by several boraginaceous plants, such as Lithospermum erythrorhizon and Arnebia euchroma. Phytochemical studies utilizing both L. erythrorhizon and A. euchroma cultured cells indicated the existence of a competing route branching out from the shikonin biosynthetic pathway to shikonofuran. A previous study has shown that the branch point is a putative alcohol dehydrogenase converting (Z)-3''-hydroxygeranylhydroquinone [(Z)-3''-OH-GHQ] to an aldehyde intermediate (E)-3''-oxo-GHQ. However, the enzyme involved in the branch reaction is not known yet. In this study, we discovered a candidate gene belonging to the cinnamyl alcohol dehydrogenase (CAD) family, AeHGO, through coexpression analysis of transcriptome data sets of shikonin-proficient and shikonin-deficient cell lines of A. euchroma. In biochemical assays, purified AeHGO protein reversibly oxidized (Z)-3''-OH-GHQ to produce (E)-3''-oxo-GHQ followed by reversibly reducing (E)-3''-oxo-GHQ to (E)-3''-OH-GHQ, resulting in an equilibrium mixture of the three compounds. Time course analysis and kinetic parameters showed that the reduction of (E)-3''-oxo-GHQ was stereoselective and efficient in presence of NADPH, which determined the overall reaction proceeded from (Z)-3''-OH-GHQ to (E)-3''-OH-GHQ. Considering a competition for accumulation between shikonin derivatives and shikonofuran derivatives in both L. erythrorhizon and A. euchroma cultured cells, AeHGO is supposed to play an important role in the metabolic regulation of the shikonin biosynthetic pathway. Characterization of AeHGO should help expedite the development of metabolic engineering and synthetic biology toward production of shikonin derivatives.